Judges’ Acceptance of Sharia-Inspired Laws in Indonesia - Kusmayanti, Hazar; Kania, Dede; Prasetyoningsih, Nanik; Zainol, Zinatul Ashiqin (Al-Manahij: Jurnal Kajian Hukum Islam, 2023)
It is fascinating how customary laws are accepted by judges in the Indonesian legal system. In Aceh, particularly, its customary law is inspired by sharia or Islamic law. In addition to the national law, this law also influences judges’ consideration in making their decisions. According to Van Den Berg’s theory of receptio in complexu, Islamic law has been recognized in Indonesian legal system as a customary law. This article tries to find out how judges accept sharia-inspired customary law to pass their decisions. The research used normative-legal method. Based on the research results, the author concluded the judge’s acceptance of customary law could be seen from a Sharia Court decision related to customary disputes. This decision was passed by the Takengon Sharia Court under No. 269/Pdt.G/2017/Ms-Tkn dated May 2, 2018. It concerned with the division of joint property. This decision referred to Islamic law in giving each party a half of the total assets after being deducted by the joint debts. This decision strengthened the foothold of Islamic law in customary law and national law enforcement, especially in Aceh Province. However, it would be a different case if the customary law was in conflict with Islamic law. In such a case, the panel of judges would not accept the customary law. An example of this was the case of adopted children. Rather than receiving an inheritance, as in the traditional parental communities, they would only receive a mandatory will. One of such decisions was the Aceh Sharia Court’s Decisions No. 125/Pdt.G/2011/MS and No.084/ Pdt.P/2016/MS.Bna.